Carbon Detection Using an HPGe Detector - ALEXA, Petr (GeoScience Engineering, 2023)
Fast neutron activation analysis has been applied to bulk carbon detection. DT-neutron generator emitting 14.1 MeV neutrons was used as a neutron source. Prompt 4.44 MeV gammas from the inelastic neutron scattering on carbon were detected using a 30% HPGe semiconductor gamma spectrometer shielded from the primary neutron beam. The sensitivity of the experimental setup is discussed. Keywords: Activation analysis; Fast neutrons; Gamma spectrometry.